A Mixed-Method Approach for Domain Analysis in Interdisciplinary Fields Using Bibliometrics: The Case of Global Studies - Carolina Rozo-Higuera (Information)
This study answers how bibliometrics and the analysis of terminology in selected theoretical books and reference sources can allow domain analysis in interdisciplinary fields of knowledge, taking as a case study the global studies (GS) field. A mixed-methods approach was applied to answer this. First, an analysis of GS’s lexicon from three sources: (1) The Encyclopedia of Global Studies (2012), (2) The Global Studies Encyclopedic Dictionary (2014), and (3) The Palgrave Dictionary of Transnational History (2009). Second, the analysis of GS topic tendencies using bibliometrics. The results show (1) the validity of the methods used for domain analysis under the lenses of library and information science (LIS) and (2) the importance of a manual selection of sources for domain analysis and the correspondence between the methods and the application of results using integrative level classification (ILC). The author concludes that domain analysis for emergent interdisciplinary fields of knowledge benefit from quantitative approaches based on a methodology that considers terminology in various formats and can be applied not just for the global studies field. Finally, we emphasize the need for collaboration between librarians and scholars for a better understanding of the dynamics of interdisciplinary vocabularies in science.